Pengaruh Stres Kerja, Lingkungan Kerja Dan Kompetensi Terhadap Kinerja (Studi Kasus Pada Guru Smk N 4 Semarang Selama Pembelajaran Jarak Jauh) - Agung Cahyo Nugroho; Bambang Suko Priyono (Jurnal Mirai Management, 2022)
The purpose of this study was to analyze the effect of work stress, work environment and competence on teacher performance during distance learning at SMK in Semarang City. The object of this research is all civil servant teachers at SMK Negeri 4 Semarang. This study uses quantitative research with a sample of 83 teachers. Seeing the change in teaching style from conventional systems using digital, it is necessary to know how it affects the performance of teachers at SMK Negeri 4 Semarang. The analytical method used in this research is multiple linear regression. The data collection method in this study used a questionnaire with accidental techniques and the Slovin formula. Keywords: Work stress, Teacher Performance, Competence